2014
DOI: 10.1161/circep.113.000876
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Inflammation, Myocardial Injury, and Prothrombotic Response After Radiofrequency Catheter Ablation for Atrial Fibrillation

Abstract: Ninety consecutive patients undergoing elective RF catheter ablation for AF were prospectively studied. All patients >18 years old, with a © 2014 American Heart Association, Inc. Original ArticleBackground-Inflammation has been linked to the genesis of stroke in atrial fibrillation (AF) and is implicated in early recurrent arrhythmia after AF ablation. We aimed to define the time course of inflammation, myocardial injury, and prothrombotic markers after radiofrequency ablation for AF and its relation to AF rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
109
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 25 publications
(34 reference statements)
10
109
4
Order By: Relevance
“…4 Lim et al reported that an elevation of inflammatory markers predicted recurrent arrhythmias within 3 days of the procedure, but not at 3 and 6 months. 6 Those findings support the hypothesis that inflammation plays a prominent role in the etiology of ERAF after RF ablation. From this standpoint, the incidence and significance of ERAF may differ between RF and CB ablation.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…4 Lim et al reported that an elevation of inflammatory markers predicted recurrent arrhythmias within 3 days of the procedure, but not at 3 and 6 months. 6 Those findings support the hypothesis that inflammation plays a prominent role in the etiology of ERAF after RF ablation. From this standpoint, the incidence and significance of ERAF may differ between RF and CB ablation.…”
Section: Resultssupporting
confidence: 70%
“…25 Relatively lower hs-CRP levels might be related to the lack of endothelial damage with cryoablation, whereas the freeze/thaw process with cardiomyocyte swelling and membrane rupture might induce greater release of myocardial injury markers. Prior studies speculated that the inflammatory response could be partly explained by local myocardial injury in RF ablation because of the positive correlation between hs-CRP elevation and markers of myocardial injury, 6 but according to our study results that did not seem applicable to CB ablation.…”
Section: Markers Of Inflammationcontrasting
confidence: 84%
See 1 more Smart Citation
“…Interruption or reduction of blood flow between cryoballoon and myocardial tissue due to improved contact force by cryoballoon might have led to lower temperatures. Improved contact of cryobal- [14] has shown that post-ablation TnT levels were associated with early AF recurrence occurring within the first three days after ablation whereas there was no association with AF recurrence in three and six months. Casella et al [6] found no association between post-CA levels of CK-MB and TnI with AF recurrence during the follow-up visits at one, three, six, and 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Recent biochemical data have shown that the postablation inflammatory phase is usually limited to the first month after PVI, 12 and a study of heart rate variability changes has also demonstrated the spontaneous recovery of transient autonomic dysfunction by 1 month. 7 Histological studies have described the formation of well-demarcated homogenous lesions by 1 week after ablation.…”
mentioning
confidence: 99%